Leisure as a Field of Study in Higher Education - Mazurek, Kas`; Dawson, Don (Canadian Journal of Higher Education, 1989)
Leisure Studies is an emerging field of study in higher education, which is engaged in a struggle for academic legitimacy in Canada and elsewhere. The field and its research endeavours can be said to be characterized by a lack of paradigmatic maturity which may best be resolved by the philosophical questioning of the fundamental principles underlying its discourse. Toward this end, a metaphysics of leisure study is urged. In this way, a distinct identity for the field may develop. Leisure Studies, finally, is not an academic "discipline", but rather a multidisciplinary field of study distinguished by its substantive area of inquiry. The present paper is most directly a commentary on the state of Leisure Studies and research in Canadian universities, but many of its observations apply to the U.S.A. and Britain as well.